Moisture-driven local strain development in ASR-damaged concrete - Seren Azad; Pavel Trtik; Markus Strobl; Anders Kaestner (PLoS ONE, 2026)
Although alkali–silica reaction (ASR) is widely recognized as one of the major concrete durability issues, the mesoscale response of pre-existing ASR products to moisture exposure remains poorly understood. In this study, neutron tomography combined with image registration is employed to non-destructively quantify moisture-induced local deformation in concrete specimens already affected by ASR damage. Three concrete mixes with different aggregate reactivities were imaged before and after 72 hours of water exposure. The resulting volumetric strain fields show that the largest localized expansions are concentrated within the crack network of the cement paste, where amorphous ASR products are expected to be prevalent. In contrast, cracks within aggregates, which typically contain crystalline ASR phases, exhibit substantially lower expansion. These observations provide direct experimental evidence supporting the hypothesis that amorphous ASR products possess a greater swelling potential than crystalline counterparts.